Usability criteria for Business Intelligence Reports in the South African banking industry - Pheladi A. Lebotsa; Judy van Biljon; Ronell van der Merwe (South African Journal of Information Management)
Background: The South African banking sector is renowned as world-class, exhibiting ample capital, cutting-edge technology, robust infrastructure, and a rigorous regulatory and supervisory framework. Business intelligence systems are fundamental to providing the data-driven decision support needed to keep the banking industry competitive. The problem is that many business intelligence (BI) reports are not used optimally, or not used at all, because of usability problems.